2004
DOI: 10.1016/j.ccr.2004.06.022
|View full text |Cite
|
Sign up to set email alerts
|

PTEN activation contributes to tumor inhibition by trastuzumab, and loss of PTEN predicts trastuzumab resistance in patients

Abstract: The ErbB2-targeting antibody, trastuzumab (Herceptin), has remarkable therapeutic efficacy in certain patients with ErbB2-overexpressing tumors. The overall trastuzumab response rate, however, is limited and what determines trastuzumab response is poorly understood. Here we report that PTEN activation contributes to trastuzumab's antitumor activity. Trastuzumab treatment quickly increased PTEN membrane localization and phosphatase activity by reducing PTEN tyrosine phosphorylation via Src inhibition. Reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
1,294
9
20

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,616 publications
(1,399 citation statements)
references
References 51 publications
61
1,294
9
20
Order By: Relevance
“…It is not clear whether or not targeting single PI3K isoforms will be successful in cancer therapy, and whether PI3K inhibitors will be effective as single agents. Collective data indicate that they will be of value in combination therapy: PI3K inhibitors have been shown to reverse resistance to trastuzumab (herceptin, a monoclonal antibody directed against ERBB2), which was caused by the loss of PTEN 123 .…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…It is not clear whether or not targeting single PI3K isoforms will be successful in cancer therapy, and whether PI3K inhibitors will be effective as single agents. Collective data indicate that they will be of value in combination therapy: PI3K inhibitors have been shown to reverse resistance to trastuzumab (herceptin, a monoclonal antibody directed against ERBB2), which was caused by the loss of PTEN 123 .…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…To elucidate the ErbB2 downstream signals that contribute to ErbB2-mediated breast cancer metastasis, we previously established in ErbB2-low-expressing MDA-MB-435 human breast cancer cells stable transfectants expressing either two ErbB2 mutants (V659E, a constitutive active form of ErbB2; K753M, a kinasedefective mutant), a wild-type ErbB2 or a control pcDNA3 vector ( Figure 1a and Nagata et al, 2004;Tan et al, 2005). We showed that the wild-type ErbB2-overexpressing 435.eB cells, ErbB2-activated V659E cells had increased tyrosine phosphorylation levels and kinase activities, and were more invasive in vitro and more metastatic in an animal model than the ErbB2 low-expressing parental MDA-MB-435 cells, control 435.neo cells and ErbB2 kinase-defective K753M cells (Tan et al, 2005).…”
Section: Upregulation and Activation Of Pkca By Erbb2mentioning
confidence: 99%
“…Reverse immunoprecipitation (IP) with an Src antibody (Figure 3b) also showed increased Src and PKCa association in ErbB2-activated cells. To test whether ErbB2 activates PKCa through Src, the 435.neo and 435.eB cells were treated with 5 or 10 mM PP2, an Src-specific inhibitor that has been shown to effectively block Src activation in these cells (Nagata et al, 2004;Tan et al, 2005). The results showed that PP2 inhibited the expression of PKCa and reduced PKCa phosphorylation in ErbB2-overexpressing cells to levels similar to that in the 435.neo cells, whereas PP2 only inhibited PKCa phosphorylation to a lesser degree in 435.neo cells (Figure 4a).…”
Section: Erbb2 Activates Pkca Through Src Kinasementioning
confidence: 99%
See 1 more Smart Citation
“…Akt regulates diverse cellular processes such as apoptosis, cell proliferation, differentiation, migration and angiogenesis. Furthermore, a number of studies have shown that overexpression and/or activation of Akt renders tumour cells resistant to chemotherapeutic drugs and signalling pathway inhibitors such as Gleevec, Iressa and Herceptin [21]. siRNA-mediated knockdown of Akt significantly reduces tumor growth and invasiveness and induces apoptosis [23].…”
mentioning
confidence: 99%